Conflict Theory On The Relationship Between Gang Violence And Haitis’s Political Crisis - Firman Anshari; Halilintar Cakra Negara; Tomy Hari Saputra; Rahaldy Briwijaya (Kajian Hukum, 2026)
This article examines the relationship between gang violence and political crisis in Haiti through the lens of conflict theory. Social, economic, and political inequalities serve as the primary factors driving the emergence and strengthening of gangs, particularly in the context of weak state institutions. Structural injustices create disparities that push marginalized groups to seek alternative sources of power through criminal activities. By analysing Haiti’s political history, this study explores how structural inequalities have exacerbated gang violence and deepened political instability. Furthermore, the role of power actors, both domestic and international, is examined in either reinforcing or mitigating this phenomenon. This study aims to provide a deeper understanding of the nexus between organized crime and chronic political instability, while also proposing policy-based solutions to curb the escalation of violence in Haiti.